2015
DOI: 10.1111/cts.12323
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and Paclitaxel Alter the Expression Pattern of miR‐143/145 and miR‐183/96/182 Clusters in T24 Bladder Cancer Cells

Abstract: Although cisplatin‐based chemotherapy is considered to be the treatment of choice for metastatic bladder cancer, its efficacy and tolerability has proven to be limited. MicroRNAs are small noncoding RNAs, whose genes are frequently organized in clusters. These molecules constitute posttranscriptional regulators of mRNA expression and are claimed to be deregulated in cancer. miR‐143/145 and miR‐183/96/182 clusters have been extensively studied in bladder cancer cells. Herein, we tried to add up to this knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“… 19 miR-21 regulates cell proliferation and migration by targeting PTEN and p53 in BC. 20 miR-202, 21 miR-212, 22 miR-222, 23 miR-429, 24 miR-200, 25 miR-210, 26 miR-214, 27 miR-182, 28 miR-99a, 29 miR-100 30 and miR-138 31 were reported in BC studies, which were mostly dependent on cell lines. The studies on miRNA relationship with BC survival were insufficient.…”
Section: Discussionmentioning
confidence: 98%
“… 19 miR-21 regulates cell proliferation and migration by targeting PTEN and p53 in BC. 20 miR-202, 21 miR-212, 22 miR-222, 23 miR-429, 24 miR-200, 25 miR-210, 26 miR-214, 27 miR-182, 28 miR-99a, 29 miR-100 30 and miR-138 31 were reported in BC studies, which were mostly dependent on cell lines. The studies on miRNA relationship with BC survival were insufficient.…”
Section: Discussionmentioning
confidence: 98%
“…Owing to these findings’ paclitaxel can be used as a therapeutic approach in synergy with geridonim for gastric as well as bladder cancer. In bladder cancer, pacliaxel up-regulates the expression of miR-143 which post-transcriptionally inhibits the expression of Akt [ 134 ].…”
Section: Paclitaxelmentioning
confidence: 99%
“…Another tumor suppressor of MPM is represented by miR-145, which is lost in MPM and acts by downregulation of OCT4 and ZEB1 [86]. Cisplatin and paclitaxel upregulated the miR-145 level in bladder cancer cells while miR-145 expression sensitized gallbladder cancer to cisplatin by MRP1 suppression [87,88]. In contrast to that, miR-17–5p expression was high in short survivors of MPM and suppression of miR-17–5p targeting p21 led to increased cisplatin sensitivity of gastric cancer cells [23,89].…”
Section: Platinum Complexes and Their Interactions With Non-coding Rnmentioning
confidence: 99%
“…It was observed that cisplatin treatment led to the induction of tumor suppressor miRNAs (let-7c, miR-34a, miR-145, miR-451) and suppression of oncomirs (miR-210) and, thus, cisplatin can potentiate the efficacy of other chemotherapeutic drugs which depend significantly on the regulation of these miRNAs (Fig. 4) [44,61,87,88].
Fig.
…”
Section: Platinum Complexes and Their Interactions With Non-coding Rnmentioning
confidence: 99%